Pseudocyst of the Pancreas on Pancreas Divisum in Children: Case Report - Amoussou, Codjo Aristide Médard; Lafia, Koto Toualouth; Gogan, Mahunakpon Vihotogbé Léon Samuel Boris; Adjadohoun, Sonia; Safari, Kunaba. D.; Metchihoungbe, Codjo Serge; Fiogbé, Michel Armand (British Journal of Healthcare and Medical Research, 2023)
Introduction: pancreatic pseudocysts (PKP) are rare with various causes. Management is non-consensual but consists of either cystic shunt or cystic excision. In accordance with the SCARE criteria, we report here the case of a 6-year-old child who presented with PKP due to acute pancreatitis and was managed by cysto-gastrostomy with simple follow-up. Clinical case: A 6-year-old girl was seen for periumbilical pain radiating to the spine and hypochondria and evolving for 3 weeks. The pain was of moderate intensity and had no sedative or triggering factors. It appeared in a non-traumatic context and apyrexia. On examination, the abdomen was distended with palpatory pain and a renal, matt mass occupying the periumbilical region, the left hypochondrium and the left flank. Ultrasound and abdominal CT scan showed a heterogeneous mass of the head of the pancreas with dilatation of the duct of Wirsung. The amylasemia was 521 IU/L and the lipaemia was 309 IU/L. The diagnosis of pseudocyst of the pancreas on acute pancreatitis was retained. She underwent trans-gastric cystic marsupialization with cysto-gastric bypass. The postoperative course was simple with a total regression of pain and a progressive weight regain. Conclusion: Acute pancreatitis is a frequent etiology of PKP that should be treated appropriately to avoid its occurrence.